Development of Canva-Based Interactive PPT Learning Media on The Material of Skeleton, Joints And Muscles to Link Interest and Motivation Elementary Students - Rahma, Isna Maulita; Aprilia, Devi Nurrochmah; Rafsanjani, Ali Akbar Rajif; Murni, Arie Widya; Bhuie, Manmeet Kaur (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
This study aims to design learning media with an interactive PPT base through Canva in IPAS subjects by focusing on material related to the skeleton, joints and muscles. This research utilizes the research & development (R&D) method with the application of the ADDIE model. The subjects of this study included students of grade VI elementary school. The research data were collected using three main methods, namely observation, questionnaires and tests and then analyzed descriptively in quantitative and qualitative approaches. This study provides results that the learning media developed has high validity on the average score of validation with a large 89% given by media experts and teachers. The application of this learning media in the classroom succeeded in increasing student learning motivation from 67% to 85%. In addition, the average student score on the test also increased, from 68 on the pretest to 85 on the posttest, indicating an increase of 25%. The developed learning media is expected to be an innovative solution for teachers in increasing students' interest, motivation, and understanding.